Biological control of silverleaf whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) using predatory bugs, Dicyphus hesperus (Hemiptera: Miridae) and Orius insidiosus (Hemiptera: Anthocoridae) - Dumont, François; Maisonhaute, Julie-Éléonore; Labrie, Geneviève; Provost, Caroline (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2021)
The silverleaf whitefly (SLW), Bemisia tabaci, is an exotic pest that causes sporadic crop damage in Canadian greenhouses, mainly on tomatoes. Its plant feeding is responsible for both direct damage as well as the transmission of plant viruses. Interestingly, omnivorous predators, which are used as biological control agents for multiple whitefly species, can establish on greenhouse crops even before the pest has established, using alternative food resources and host plants to support the predator. However, the efficiency of such indigenous omnivorous biological agents in the suppression of high density and intense SLW infestations remains unknown. This research aimed to assess the potential of two indigenous omnivorous biological agents, Dicyphus hesperus and Orius insidiosus to control SLW infestations and their effects on tomato plant health and yield at both early stages of the crop cycle, and at high pest densities. This study showed that populations of B. tabaci are able to grow rapidly. However, neither of the introduced densities of B. tabaci nor the infestation time had a significant effect on the incidence of tomato irregular ripening disorder (TIR) and yield. Our results also show that the introduction of three or five D. hesperus adults per cage reduces the number of B. tabaci larvae and pseudo-nymphs, while O. insidiosus did not significantly reduce SLW populations. Our results suggest that D. hesperus could control high levels of SWL and at an early stage in the cropping cycle.